Artificial Intelligence dan Tantangan Ideologi Bangsa: Relevansi Pancasila di Era Digital - Nur Kholis Majid (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
The development of Artificial Intelligence is moving fast and it is a big problem for the values that Indonesia is based on which is Pancasila. The main goal of this study is to look at the problems that Pancasila is facing because of Artificial Intelligence and to see if Pancasila is still a framework for guiding Artificial Intelligence in Indonesia. The method used to do this research is by looking at the laws and the ideas, behind them. This is done by studying the laws and the concepts that are related to Artificial Intelligence and Pancasila. The research results show that the development of AI has posed challenges in the form of: (1) religious disinformation and degradation of spirituality; (2) algorithmic bias, privacy violations, and dehumanization; (3) filter bubbles, echo chambers, and algorithmic manipulation; (4) manipulation of public opinion and unaccountable decision-making; (5) digital divide and concentration of economic power. The values of Pancasila are relevant as a normative framework for AI governance in Indonesia and can be translated into concrete AI ethical principles such as: (1) the principle of dignified AI; (2) the principle of fair and empathetic AI; (3) the principle of AI that strengthens social cohesion; (4) the principle of accountable and democratic AI; (5) the principle of equitable and inclusive AI.